CONTEMPORARY ISLAMIC THOUGHT: Challenges and Solutions in Da'wah in the Digital Era - Srigita, Ferty Deseliyana; Rifa'i, Akhmad (Jurnal Al-Ulum : Jurnal Pemikiran dan Penelitian Ke-Islaman, 2025)
Contemporary Islamic thought in da'wah faces major challenges in the digital era, including the rapid development of information technology that affects people's understanding of Islamic teachings and the increasing flow of secular and liberal thought. On the one hand, the digital era provides a great opportunity to spread Islamic values more widely and effectively. This research aims to examine the challenges faced by contemporary Islamic da'wah in the digital era and offer relevant solutions. The research method used is a literature study with a qualitative approach, which analyzes various sources related to Islamic thought, da'wah, and digital technology. The results of the study show that the first challenge faced by Islamic da'wah in the digital era is the shift in communication media. The second challenge is the issue of religious authority in digital da'wah. Digital platforms allow anyone to express their views on religion, including those who do not have an adequate religious education background. To overcome these challenges, contemporary Islamic thought offers several solutions in the context of da'wah in the digital era. The first solution is to develop a more creative and adaptive da'wah approach to technology. The second is the importance of verifying and curating da'wah information in digital media. The implication of this research is that contemporary Islamic thought faces the challenges of digitalization, but also offers innovative da'wah solutions. The wise use of technology can increase the effectiveness of the spread of moderate and relevant Islamic teachings for modern society.